2009
DOI: 10.1210/jc.2008-1624
|View full text |Cite
|
Sign up to set email alerts
|

Euthyroid Hyperthyrotropinemia in Children Born after in Vitro Fertilization

Abstract: A significant elevation of serum TSH compatible with a mild TSH resistance of the thyroid were found in IVF children compared with controls. This was not due to the presence of antithyroid autoantibodies. We suggest that this might represent a slight epigenetic developmental abnormality related to the preimplantation manipulation of the embryo. Further studies are needed to confirm these findings and to better determine their etiopathogenesis and clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 19 publications
1
37
0
3
Order By: Relevance
“…Genetic imprinting diseases, such as the Beckwith-Wiedemann and Angelman syndromes, have been associated with assisted reproduction, mainly ICSI (4,35,36) and we have also recently reported a higher incidence of euthyroid hyperthyrotropinemia in children conceived by IVF compared with controls, reminiscent of an epigenetic modification of the TSH set point in these children (37). Therefore, more research needs to be conducted in children conceived by IVF as periconceptual manipulations may influence their future health outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Genetic imprinting diseases, such as the Beckwith-Wiedemann and Angelman syndromes, have been associated with assisted reproduction, mainly ICSI (4,35,36) and we have also recently reported a higher incidence of euthyroid hyperthyrotropinemia in children conceived by IVF compared with controls, reminiscent of an epigenetic modification of the TSH set point in these children (37). Therefore, more research needs to be conducted in children conceived by IVF as periconceptual manipulations may influence their future health outcome.…”
Section: Discussionmentioning
confidence: 96%
“…The finding is more common in children born premature [120], small for gestational age [121] and after in vitro fertilization [122] as well as in those with trisomy 21 [123]. In a small proportion of cases a mild morphological abnormality in thyroid gland development [124] or genetic defect in thyroid hormonogenesis has been demonstrated, the latter including mutations in the genes for the TSH receptor [124,125,126], dual oxidase 2 [127] and thyroid peroxidase [124].…”
Section: Sch In Childhoodmentioning
confidence: 99%
“…In addition, Sakka et al [33] demonstrated a significantly higher prevalence of SH in children aged 4 to 14 years, conceived after IVF than in the control group, in the absence of detectable thyroid antibodies. A possible explanation provided by the authors was an epigenetic developmental abnormality in the set point of TSH sensitivity related to the preimplantation manipulation of the embryo [33]. …”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%